Keanekaragaman Komunitas Artropoda Predator Tanaman Padi yang Aplikasi Boinsektisida Berbasis Jamur Entomopatogen Daerah Rawa Lebak Sumatera Selatan - khodijah khodijah (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2013)
Species diversity and abundance of canopy-inhabiting and soil-dwelling arthropods could be affected by pesticide application. Population and the intensity of the rice stem borer attack can influence pesticide application. This study aimed to examine the effect of the application of solid and liquid bio insecticide entomopathogenic fungus Beauveria bassiana-based formulations on species diversity and abundance of predatory arthropods in inhabiting paddy canopy and soil dwelling. The research was conducted in fresh-water swamp rice cultivation in Pelabuhan Dalam village, Pemulutan district, Ogan Ilir regency in South Sumatra, from Mei to Agustus 2012. The results showed that the application of liquid and solid bioinsecticida affected predatory arthropods diversity (H') at rice plant canopy. The highest effect was found in rice plant applied with liquid bio insecticide and the lowest effect with synthetic insecticides. Predatory arthropods diversity (H') in soil dwelling was the highest in rice plants applied with solid bioinsecticide and the lowest with synthetic insecticides